The European Union control strategy for Campylobacter spp. in the broiler meat chain. Issue 5 (8th June 2020) - Nastasijevic, Ivan; Proscia, Francesco; Boskovic, Marija; Glisic, Milica; Blagojevic, Bojan; Sorgentone, Simona; Kirbis, Andrej; Ferri, Maurizio
Abstract: Campylobacter is the most common cause of bacterial gastroenteritis worldwide and the most frequently reported foodborne pathogen in the European Union (EU). While campylobacteriosis is generally self‐limiting, some patients could develop severe sequelae. The predominant source of infection is poultry. This review addresses the most relevant factors influencing the prevalence and contamination level of Campylobacter spp. in the poultry chain continuum. The emphasis was put on the novel control strategy for Campylobacter that is based on evidence‐based risk assessment and the introduction of process hygiene criterion intended for monitoring the prevalence and counts of Campylobacter spp. on broiler carcasses at slaughter level. The reduction of Campylobacter spp. in the poultry meat chain in the EU can only be achieved with an integrated meat safety assurance approach. This includes primary interventions at the level of the poultry farm, implementation of effective control measures at slaughterhouses, and fostering awareness campaigns aimed at consumers. Abstract : Campylobacter is the most common cause of bacterial gastroenteritis worldwide and the most frequently reported foodborne pathogen in the European Union (EU). The predominant source of infection is poultry. The reduction of Campylobacter spp. in the poultry meat chain in the EU can only be achieved with an integrated meat safety assurance approach.